A multifaceted comparative analysis of image and video technologies in gastrointestinal endoscope and their clinical applications - Chen, Yuequn; Wu, Guiqiong; Qu, Chaojun; Ye, Zimao; Kang, Yihao; Tian, Xin (Frontiers in Medicine, 2023)
This paper presents a comprehensive exploration of endoscopic technologies in clinical applications across seven tables, each focusing on a unique facet of the medical field. The discourse begins with a detailed analysis of pediatric endoscopes, highlighting their diagnostic capabilities in various conditions. It then delves into the specifications and applications of globally recognized capsule endoscopy devices. Additionally, the paper incorporates an analysis of advanced imaging techniques, such as Narrow Band Imaging (NBI), Flexible Spectral Imaging Color Enhancement (FICE), and i-scan, which are increasingly being integrated into ultrathin gastrointestinal (GI) endoscopes. Factors like technological capabilities, light source, camera technology, and computational constraints are evaluated to understand their compatibility with these advanced imaging techniques, each offering unique advantages and challenges in clinical settings. NBI, for instance, is lauded for its user-friendly, real-time enhanced imaging capabilities, making it effective for early detection of conditions like colorectal cancer and Barrett’s esophagus. Conversely, FICE and i-scan offer high customizability and are compatible with a broader range of endoscope models. The paper further delves into innovative advances in movement control for Nasojejunal (NJ) feeding tube endoscopy, elucidating the potential of AI and other novel strategies. A review of the technologies and methodologies enhancing endoscopic procedure control and diagnostic precision follows, emphasizing image and video technologies in pediatric endoscopy, capsule endoscopes, ultrathin endoscopes, and their clinical applications. Finally, a comparative analysis of leading real-time video monitoring endoscopes in clinical practices underscores the continuous advancements in the field of endoscopy, ensuring improved diagnostics and precision in surgical procedures. Collectively, the comparative analysis presented in this paper highlights the remarkable diversity and continuous evolution of endoscopic technologies, underlining their crucial role in diagnosing and treating an array of medical conditions, thereby fostering advancements in patient care and clinical outcomes.